PvdQ Quorum Quenching Acylase Attenuates Pseudomonas aeruginosa Virulence in a Mouse Model of Pulmonary Infection - Utari, Putri D.; Setroikromo, Rita; Melgert, Barbro N.; Quax, Wim J. (Frontiers in Cellular and Infection Microbiology, 2018)
Pseudomonas aeruginosa is the predominant pathogen in pulmonary infections associated with cystic fibrosis. Quorum sensing (QS) systems regulate the production of virulence factors and play an important role in the establishment of successful P. aeruginosa infections. Inhibition of the QS system (termed quorum quenching) renders the bacteria avirulent thus serving as an alternative approach in the development of novel antibiotics. Quorum quenching in Gram negative bacteria can be achieved by preventing the accumulation of N-acyl homoserine lactone (AHL) signaling molecule via enzymatic degradation. Previous work by us has shown that PvdQ acylase hydrolyzes AHL signaling molecules irreversibly, thereby inhibiting QS in P. aeruginosa in vitro and in a Caenorhabditis elegans model of P. aeruginosa infection. The aim of the present study is to assess the therapeutic efficacy of intranasally instilled PvdQ acylase in a mouse model of pulmonary P. aeruginosa infection. First we evaluated the deposition pattern of intranasally administered fluorochrome-tagged PvdQ (PvdQ-VT) in mice at different stages of pulmonary infection by in vivo imaging studies. Following intranasal instillation, PvdQ-VT could be traced in all lung lobes with 42 ± 7.5 % of the delivered dose being deposited at 0 hour post bacterial-infection, and 34 ± 5.2 % at 72 hours post bacterial-infection. We then treated mice with PvdQ during lethal P. aeruginosa pulmonary infection and that resulted in a five-fold reduction of lung bacterial load and a prolonged survival of the infected animals. In a sublethal P. aeruginosa pulmonary infection, PvdQ treatment resulted in less lung inflammation as well as lower levels of CXCL2 and TNF-α. In conclusion, our study has shown therapeutic efficacy of PvdQ acylase as a quorum quenching agent during P. aeruginosa infection.